Product Change in a Small Company: Effects on Eco-price and Global Productivity - Carvalho, Nilson [UNESP]; Giannetti, Biagio Fernando [UNESP]; Agostinho, Feni [UNESP]; Villas Boas de Almeida, Cecilia Maria [UNESP]; Grabot, B.; Vallespir, B.; Gomes, S.; Bouras, A.; Kiritsis, D. (Springer, 2014)
The notion of supply chain thinking working to reduce the environmental and socioeconomic burden associated with a manufactured product or selection of products throughout their value chain was recently recognized. However, there are also several types of small businesses that arise in the sphere of influence of large supply chains in order to fill gaps or serve customers with special needs, which have not been considered or assessed. These small companies, in general, have little or none influence on decisions made along the entire supply chain, and have to adapt their production processes induced by decisions made by the leading companies within the chain. This work assesses the changes in the environmental resource use of a small company operating in the Brazilian automotive aftermarket using emergy synthesis and confirms the idea that the supply chain thinking works to reduce the environmental reducing the burden associated with products manufacturing within the value chain. The simulation performed for the period 2014-2025, within the company's business plan, shows that the sooner the exchange of products is made, the greater the profits of the company with regard to eco-efficiency and environmental responsibility.
Keywords: emergy; automotive aftermarket; resource use; eco-price